Automatic process control in anaerobic digestion technology: A critical review. (October 2015) - Nguyen, Duc; Gadhamshetty, Venkataramana; Nitayavardhana, Saoharit; Khanal, Samir Kumar
Highlights: Critical review on automatic controls for diverse scales of AD processes. Monitoring in AD system was focused in chromatography and spectrometry techniques. Advanced controls are usually equipped with simple sensors and vice versa. Centralized AD plants could promote applications of automatic controls. Abstract: Anaerobic digestion (AD) is a mature technology that relies upon a synergistic effort of a diverse group of microbial communities for metabolizing diverse organic substrates. However, AD is highly sensitive to process disturbances, and thus it is advantageous to use online monitoring and process control techniques to efficiently operate AD process. A range of electrochemical, chromatographic and spectroscopic devices can be deployed for on-line monitoring and control of the AD process. While complexity of the control strategy ranges from a feedback control to advanced control systems, there are some debates on implementation of advanced instrumentations or advanced control strategies. Centralized AD plants could be the answer for the applications of progressive automatic control field. This article provides a critical overview of the available automatic control technologies that can be implemented in AD processes at different scales.